The impact of tourism on the Jordanian economy - Al-Shabbar, Khaled Jehad Issa (2016)
The world is heading to improve tourism sectors. And so do Jordan. Currently, tourism is Jordan’s important foreign exchange generator. Tourism, one of the world’s largest and fastest growing industries is a strategic factor for the economic growth. Since the empirical results associated with the relationship among economic growth and tourism within neoclassical framework are inconsistent, this study has been placed to show that tourism sector has a role in the economic growth using the Jordanian context by using data from 1981-2014. The objectives are to determine the long run and the short run relationships among economic growth, tourism receipts, and government tourism expenditures. The study employs econometric techniques such as unit roots, Johansen cointegration, and Error Correction Model (ECM). the results from Johansen cointegration show a positive and statistically significant relationship between tourism receipts and economic growth. On the other hand, the test shown negative and significant relationship among government tourism expenditures and economic growth. Short run relationships expose only tourism receipts is significant and positively related to growth. The coefficient of the speed of adjustment was not high when there is a state of disequilibrium. Besides improving the present knowledge, the findings also proposed to policy makers to further improve and sustain tourism sector in order to generate higher economic growth